ANALISIS GREEN ACCOUNTING DAN NILAI PERUSAHAAN TERHADAP PROFITABILITAS PADA SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Dhea Adlia; Nova Novita (Journal of Accounting, Management and Islamic Economics, 2025)
This study aims to determine the effect of green accounting and company value on profitability. This study uses data from 18 manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange from 2018 to 2022. The sampling technique used in this study is purposive sampling with predetermined criteria. The research method used in this study is multiple linear regression analysis using E-views 12 software. The results of this study indicate that green accounting does not have a negative effect on profitability and that company value has a positive effect on profitability.